2005
DOI: 10.1189/jlb.0705377
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression changes by amyloid β peptide-stimulated human postmortem brain microglia identify activation of multiple inflammatory processes

Abstract: A central feature of the inflammatory pathology in Alzheimer's disease is activated microglia clustered around aggregated amyloid beta (Abeta) peptide-containing plaques. In vitro-cultured microglia can be activated to an inflammatory state by aggregated Abeta with the induction of a range of different neurotoxic factors and provide a model system for studying microglia Abeta interactions. Gene expression responses of human postmortem brain-derived microglia to aggregated Abeta were measured using whole genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 79 publications
6
138
1
Order By: Relevance
“…The aggregated Ab protein, which is present in senile plaques of AD patients, activates microglia to produce neurotoxic substances that contribute to the neurodegenerative changes [41][42][43][44]. In accordance with previous reports in AD and AD animal models, we wondered whether activated microglia by BM-MSCs produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 61%
“…The aggregated Ab protein, which is present in senile plaques of AD patients, activates microglia to produce neurotoxic substances that contribute to the neurodegenerative changes [41][42][43][44]. In accordance with previous reports in AD and AD animal models, we wondered whether activated microglia by BM-MSCs produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 61%
“…Activation of microglia results in the production of NO, oxygen free radicals, proteases, adhesion molecules and proinflammatory cytokines such as TNFα, IL-1β, LT-α, and IL-6 [27][28][29][30][31]. It is thought that the overproduction of these inflammatory mediators is important in the degenerative process in patients with AD [32].…”
Section: Tlrs In Alzheimer's Diseasementioning
confidence: 99%
“…In humans, high synovial fluid levels S100A8/A9 are measured in rheumatoid arthritis; concentration increases with disease severity and resistance to treatment (Frosch et al, 2000). S100A8 mRNA expression is greatly induced by β-amyloid in microglia cultured from post-mortem human brain tissue (Walker et al, 2006), while S100A9 protein is found in reactive microglia in Alzheimer's disease brains (Akiyama et al, 1994). Excessive levels of calprotectin can induce symptoms of zinc deficiency and reduced resistance to infection (Sampson et al, 2002), common conditions in the elderly.…”
Section: S100a8 and S100a9mentioning
confidence: 99%